Seed endophytes of malting barley from different locations are shaped differently and are associated with malt quality traits - Oyeyemi Ajayi; Ramamurthy Mahalingam (BMC Plant Biology)
Abstract Maximizing microbial functions for improving crop performance requires better understanding of the important drivers of plant-associated microbiomes. However, it remains unclear the forces that shapes microbial structure and assembly, and how plant seed-microbiome interactions impact grain quality. In this work, we characterized the seed endophytic microbial communities of malting barley from different geographical locations and investigated associations between microbial (bacterial and fungal) species diversity and malt quality traits. Host genotype, location, and interactions (genotype x location) significantly impacted the seed endophytic microbial communities. Taxonomic composition analysis identified the most abundant genera for bacterial and fungal communities to be Bacillus (belonging to phylum Firmicutes) and Blumeria (belonging to phylum Ascomycota), respectively. We observed that a greater proportion of bacterial amplicon sequence variants (bacterial ASVs) were shared across genotypes and across locations while the greater proportion of the fungal ASVs were unique to each genotype and location. Association analysis showed a significant negative correlation between bacterial alpha diversity indices (Faith PD and Shannon indices) and malt quality traits for barley protein (BP), free amino nitrogen (FAN), diastatic power (DP) and alpha amylase (AA), while fungal alpha diversity (Shannon and Simpson) showed significant negative relationship with β-D-glucan content. In addition, some bacterial and fungal genera were significantly associated with malt extract (ME) -a key trait for maltsters and brewers. We conclude that barley genotype, location, and their interactions shape the seed endophytic microbiome and is key to microbiome manipulation and management during barley production and/or malting.